2015
DOI: 10.3324/haematol.2015.133025
|View full text |Cite
|
Sign up to set email alerts
|

Nodular lymphocyte predominant Hodgkin lymphoma: a Lymphoma Study Association retrospective study

Abstract: Nodular lymphocyte predominant Hodgkin lymphoma represents a distinct entity from classical Hodgkin lymphoma. We conducted a retrospective study to investigate the management of patients with nodular lymphocyte predominant Hodgkin lymphoma. Clinical characteristics, treatment and outcome of adult patients with nodular lymphocyte predominant Hodgkin lymphoma were collected in Lymphoma Study Association centers. Progression-free survival (PFS) and overall survival (OS) were analyzed, and the competing risks form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…There were a low frequency of patients with early stage disease who were treated with radiotherapy alone. This might be related with some previous reports indicating a high frequency of early and late relapses in early stage patients who were initially treated with limited site radiotherapy . Immunotherapy was mainly reserved to later treatment lines.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There were a low frequency of patients with early stage disease who were treated with radiotherapy alone. This might be related with some previous reports indicating a high frequency of early and late relapses in early stage patients who were initially treated with limited site radiotherapy . Immunotherapy was mainly reserved to later treatment lines.…”
Section: Discussionsupporting
confidence: 80%
“…and extranodal involvements despite relatively high proportion of advanced stage disease.None of the patients was followed with a watchful waiting approach at our study. In a recent study of Lazarovici et al, early treatment appeared more beneficial compared to watchful waiting in terms of PFS but has no impact on overall survival 17. It is still a debate whether early stage NLPHL patients should be carefully watched without therapy or not.…”
mentioning
confidence: 99%
“…Individuals with stage I/II disease accounted for 82.5% of patients, whereas only 17.5% of patients had stage III/IV disease. 12 The median age at diagnosis (37 years and 38 years) and the proportion of male patients (75% and 77.7%) in the GHSG and LYSA studies were also comparable. 11,12 An association between a variant histology (growth pattern C-F according to Fan et al) 9 and more advanced disease at the initial NLPHL diagnosis has been demonstrated in several studies.…”
Section: Clinical Presentation (Histopathological Patterns)mentioning
confidence: 79%
“…12 The median age at diagnosis (37 years and 38 years) and the proportion of male patients (75% and 77.7%) in the GHSG and LYSA studies were also comparable. 11,12 An association between a variant histology (growth pattern C-F according to Fan et al) 9 and more advanced disease at the initial NLPHL diagnosis has been demonstrated in several studies. 7,13 A retrospective analysis from the GHSG including a total of 413 patients, indicated that 29.5% of patients with a variant histology had advanced stage disease at the time of initial NLPHL diagnosis.…”
Section: Clinical Presentation (Histopathological Patterns)mentioning
confidence: 79%
“…For the 18 remaining patients with advanced‐stage disease, 6/7 patients in the rituximab arm progressed and 5‐year PFS was only 28·6% compared to 66·7% in the non‐rituximab arm (King et al , ). Another larger retrospective study (314 evaluable cases) showed early treatment with chemotherapy or RT, but not rituximab alone, reduced the risk of progression compared to watchful waiting, even if there was no impact on OS (Lazarovici et al , ). Fanale () conducted an interesting retrospective analysis in which 12 advanced‐stage patients received R‐CHOP, with an ORR of 100%, a CR rate of 90% and no relapses or transformations after a median follow‐up of 42 months.…”
Section: Patient Characteristics Response To Treatment and Toxicitymentioning
confidence: 99%